A multigene RT-PCR assay used to predict recurrence in early breast cancer: two presentations with contradictory results - Fiets, Willem E (BioMed Central, 2004)
During the 2003 San Antonio Breast Cancer Symposium two studies were presented that were designed to validate a recurrence score, derived from a 21-gene RT-PCR assay, in patients with axillary node-negative breast cancer. This recurrence score was highly predictive for the risk of recurrence in 668 patients treated in a large multicenter trial with adjuvant tamoxifen. However, no prognostic value was found in a small group of patients who were retrospectively selected in a single institution and who did not receive any adjuvant systemic therapy. Further validation is needed to establish the prognostic and predictive role of this assay in clinical management.